Safety and efficacy of Momordica charantiaLinnaeus in pre-diabetes and type 2 diabetes mellitus patients: a systematic review and meta-analysis protocol - Peter, Emanuel L.; Deyno, Serawit; Mtewa, Andrew; Kasali, Félicien Mushagalusa; Nagendrappa, Prakash B.; Sesaazi, Duncan; Tolo, Casim Umba; Ogwang, Patrick Engeu (Systematic Reviews, 2018)
Background: Momordica charantiaLinnaeus (Cucurbitaceae) has been used traditionally as a nutritious food and asa herbal medicine for type 2 diabetes mellitus. However, human studies that investigated its glycemic control have generated inconsistent findings. Therefore, this systematic review and meta-analysis is aimed at evaluating the safety and efficacy of M. charantiaL. Preparations in human studies that have investigated its role in glycemic control. Methods: This protocol has been prepared according to Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). The review will include randomized clinical trials and non-randomized clinical trials. The included studies will have assessed glycemic control of M. Charantia preparations with placebo or standard oral anti-hyperglycemic agents in adult pre-diabetes and/or type 2 diabetes mellitus patients and have at least 4 weeks of follow-up. The primary outcomes of review are fasting blood glucose levels, glycosylated hemoglobin A1c, and post-prandial blood glucose level. Electronic database search for published literatures will be conducted without language restriction in EMBASE, MEDLINE/PubMed, the Cochrane Library, SCOPUS, Web of Sciences, and CINAHL databases. Search for gray literatures and references of the retrieved full-text articles will be conducted in Google, Google Scholar, Open Grey, Pro Quest dissertations & Theses, British Library EThos, and university digital library systems. Two independent reviewers will later evaluate full texts, extract data, and assess risk of bias of eligible articles. Publication biases will be assessed by testing asymmetry of funnel plot using Egger’s or Begg’s tests while heterogeneity will be assessed using Cochran Q test, Pvalue, andI2. Revman software version 5.3will be used for meta-analysis including subgroup and sensitivity analysis. Discussion: This systematic review and meta-analysis will investigate both safety and efficacy of M. Charantia preparations in type 2 diabetes mellitus. The review results will be published in a peer-reviewed journal. The results will bring better understanding of clinical outcomes in treatment of type 2 diabetes mellitus patients and highlight gaps for future research.
Keywords: NIDDM; Bitter gourd; Systematic review; Protocol; Meta-analysis